2017
DOI: 10.3390/atmos8010015
|View full text |Cite
|
Sign up to set email alerts
|

Projected Changes in Temperature Extremes in China Using PRECIS

Abstract: Temperature extremes can cause disastrous impacts on ecological and social economic systems. China is very sensitive to climate change, as its warming rate exceeds that of the global mean level. This paper focused on the spatial and temporal changes of the temperature extremes characterized by the 95th percentile of maximum temperature (TX95), the 5th percentile of the minimum temperature (TN5), high-temperature days (HTD) and low-temperature days (LTD). The daily maximum and minimum temperatures generated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…A series of climate scenarios with a horizontal resolution of 50 km generated from PRECIS had been used for the analysis of the average climate trend [25], changes of summer days, consecutive frost days and growing season length [26], heat wave frequency and duration [27] under SRES scenarios in the 21st century, as well as the changes of the 95th percentile of the maximum temperature, the 5th percentile of the minimum temperature, high-and low-temperature days [28], and lighting and thermal resources in the potential northward areas of winter wheat [29] (details in Table S1) under the RCP scenarios during the 21st century. In our paper, the latest version (PRECIS2.1) with a horizontal resolution of 25 km will be used to dissect AT10, PGS and FFP changes under the RCP4.5 scenario in the 21st century in Northeast China.…”
Section: Model Datamentioning
confidence: 99%
“…A series of climate scenarios with a horizontal resolution of 50 km generated from PRECIS had been used for the analysis of the average climate trend [25], changes of summer days, consecutive frost days and growing season length [26], heat wave frequency and duration [27] under SRES scenarios in the 21st century, as well as the changes of the 95th percentile of the maximum temperature, the 5th percentile of the minimum temperature, high-and low-temperature days [28], and lighting and thermal resources in the potential northward areas of winter wheat [29] (details in Table S1) under the RCP scenarios during the 21st century. In our paper, the latest version (PRECIS2.1) with a horizontal resolution of 25 km will be used to dissect AT10, PGS and FFP changes under the RCP4.5 scenario in the 21st century in Northeast China.…”
Section: Model Datamentioning
confidence: 99%
“…The number of rainstorm days to the south of the Huaihe River is mostly increasing, and to the north of the Huaihe River, the trend is to decrease (Chen et al 2010). China is also undergoing increasing weather and climate extreme events in terms of the numbers and frequencies (Ren et al 2011) and will experience much more hot extremes, less cold extremes and intensified extreme precipitation events by the end of the twenty-first century (Gao et al 2002;Zhang et al 2006;Ji and Kang 2015;Zhang et al 2017). Analyses of long-term meteorological station data showed that most parts of China have witnessed an increase in heat waves defined by the 90th percentile threshold of history record at frequencies of approximately 1 to 1.5 times per year (Ding et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, to quantify climate changes caused by CO 2 and other trace gases, physical methods using numerous global climate models, such as three-dimensional general circulation models under different emissions scenarios, are applied to construct climate scenarios [8,45,[72][73][74][75][76]. Their main disadvantage is based on the ultra-complicated and complex character of the actual climate system and the inherent inability to construct a model that can be its perfect copy [8].…”
Section: Introductionmentioning
confidence: 99%
“…With the above in mind, synthetic scenarios are a useful tool to suggest the magnitude of future spatial and temporal climatic changes at a regional scope [8,[10][11][12]24,57,76,77]. Three warming scenarios +1, +2 and +3 • C are suggested for application, as they represent simulations of temperature changes in the regions under different emission scenarios based on the consensus of the World Climate Research Programme Coupled Model Intercomparison Project [1][2][3][4][5][72][73][74][75][76][78][79][80][81][82].…”
Section: Introductionmentioning
confidence: 99%